Performance Appraisal Implementation gaps: Shifting the thinking to Organizational Capacity - Musubira, Hilda; Kagambirwe Karyeija, Gerald (Ugandan Journal of Management and Public Policy Studies, 2020)
This paper examines the drivers for effective implementation of Open Performance Appraisal (OPA) in the Ugandan civil service. It proceeds from the view that organizational culture has often been used as an explanatory variable for performance appraisal implementation. The article is based on critical review of theoretical and empirical literature on implementation drivers, the background of Uganda’s Performance Appraisal system as well as the Organization Readiness. The authors argue that change effi cacy and commitment to change are critical predictors of successful implementation of the open appraisal system in Uganda. The paper concludes that capacity and organizational culture are necessary but not suffi cient factors for effective implementation and notably, capacity is a product of organizational commitment. Similarly, a positive organizational culture can be built in face of sufficient readiness.
Keywords: Performance Appraisal; Implementation; Organizational Readiness